1989
DOI: 10.1073/pnas.86.8.2683
|View full text |Cite
|
Sign up to set email alerts
|

Acidic fibroblast growth factor mRNA is expressed by cardiac myocytes in culture and the protein is localized to the extracellular matrix.

Abstract: Acidic fibroblast growth factor mRNA is expressed by cardiac myocytes in culture and the protein is localized to the extracellular matrix ( Communicated by James B. Wyngaarden, December 9, 1988 ABSTRACT Acidic and basic fibroblast growth factors are heparin-binding proteins that induce cellular proliferation, mesodermal development, and vascular growth. As such, they may be important in cardiac development and disease. To determine whether cardiac myocytes contain fibroblast growth factors, neonatal rat car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(41 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…RNA bands of ϳ6.0, 4.2, and 3.1 kb were present, as has been described in cardiac myocytes. 19 As can be seen in Figure 8A, IL-8 induced increased levels of FGF2 mRNA as early as 6 hours after treatment. By densitometry, after normalization for variation in mRNA loading using control glyceraldehyde-3Ј-phosphate dehydrogenase hybridization a sevenfold increase in FGF2 mRNA levels was present at 6 hours, which decreased slightly by 24 hours.…”
Section: Il-8 Increases Fgf2 Mrna In Prostatic Stromal Cellsmentioning
confidence: 64%
“…RNA bands of ϳ6.0, 4.2, and 3.1 kb were present, as has been described in cardiac myocytes. 19 As can be seen in Figure 8A, IL-8 induced increased levels of FGF2 mRNA as early as 6 hours after treatment. By densitometry, after normalization for variation in mRNA loading using control glyceraldehyde-3Ј-phosphate dehydrogenase hybridization a sevenfold increase in FGF2 mRNA levels was present at 6 hours, which decreased slightly by 24 hours.…”
Section: Il-8 Increases Fgf2 Mrna In Prostatic Stromal Cellsmentioning
confidence: 64%
“…FGF1 has been localized extracellularly in vivo in the developing heart (Engelmann et al, 1993), tooth (Cam et al, 1992), lungs, digestive system, CNS and eye (Fu et al, 1991) where it is thought to act both as a paracrine growth factor as well as stimulating capillary and neural invasion. Weiner and Swain (1989) have shown that neonatal cardiac myocytes deposit FGF1 into their extracellular matrix and FGFR1 transcipts have been localized on developing cardiomyocytes (Engelman et al, 1993). Thus, tumorogenesis may mimic development in its mechanism of FGF1 action.…”
Section: Discussionmentioning
confidence: 99%
“…Both bFGF and aFGF can be detected in freshly isolated adult rat ventricular myocytes by immunohistochemistry, by Western analysis, and by immunoassay of mitogenic activity detected in myocyte cell lysates processed by heparin-Sepharose affinity chromatography (19)(20)(21)(22)59). In the intact heart, we have documented increased release by ELISA of both bFGF and aFGF in the perfusate of adult rat hearts retrogradely perfused for 5 min ex vivo in a Langendorff preparation with a physiologic saline solution containing 10 Ϫ7 M isoproterenol (60).…”
Section: Discussionmentioning
confidence: 99%
“…Both basic fibroblast growth factor (bFGF; FGF-2) and acidic fibroblast growth factor (aFGF; FGF-1) have been identified in terminally differentiated, postmitotic adult cardiac muscle cells, with subcellular localization to the cytoplasm, nucleus, and gap junctions at intercalated disks (18)(19)(20)(21)(22). FGFs released from these cells could act in an autocrine manner or on neighboring myocytes or other cell types in ventricular muscle.…”
Section: Introductionmentioning
confidence: 99%